Cardiomyocyte specific overexpression of a 37 amino acid domain of regulator of G protein signalling 2 inhibits cardiac hypertrophy and improves function in response to pressure overload in mice. (July 2017) - Lee, Katherine N.; Lu, Xiangru; Nguyen, Chau; Feng, Qingping; Chidiac, Peter
Abstract: Regulator of G protein signalling 2 (RGS2) is known to play a protective role in maladaptive cardiac hypertrophy and heart failure via its ability to inhibit Gq - and Gs - mediated GPCR signalling. We previously demonstrated that RGS2 can also inhibit protein translation and can thereby attenuate cell growth. This G protein-independent inhibitory effect has been mapped to a 37 amino acid domain (RGS2 eb ) within RGS2 that binds to eukaryotic initiation factor 2B (eIF2B). When expressed in neonatal rat cardiomyocytes, RGS2 eb attenuates both protein synthesis and hypertrophy induced by Gq - and Gs - activating agents. In the current study, we investigated the potential cardioprotective role of RGS2 eb by determining whether RGS2 eb transgenic (RGS2 eb TG) mice with cardiomyocyte specific overexpression of RGS2 eb show resistance to the development of hypertrophy in comparison to wild-type (WT) controls. Using transverse aortic constriction (TAC) in a pressure-overload hypertrophy model, we demonstrated that cardiac hypertrophy was inhibited in RGS2 eb TG mice compared to WT controls following four weeks of TAC. Expression of the hypertrophic markers atrial natriuretic peptide (ANP) and β-myosin heavy chain (MHC-β) was also reduced in RGS2 eb TG compared to WT TAC animals. Furthermore, cardiac function in RGS2 eb TG TAC mice was significantly improved compared to WT TAC mice. Notably, cardiomyocyte cell size was significantly decreased in TG compared to WT TAC mice. These results suggest that RGS2 may limit pathological cardiac hypertrophy at least in part via the function of its eIF2B-binding domain. Highlights: RGS2 eb is cardioprotective and inhibits TAC- induced cardiac hypertrophy. Heart function is maintained in RGS2 eb TG mice following TAC. RGS2 eb reduces cardiac hypertrophy following 4 weeks of TAC. Expression of cardiac hypertrophy markers is reduced in RGS2 eb TG TAC mice.